Parental Origin of Gsα Inactivation Differentially Affects Bone Remodeling in a Mouse Model of Albright Hereditary Osteodystrophy. (16th November 2021) - McMullan, Patrick; Maye, Peter; Yang, Qingfen; Rowe, David W.; Germain‐Lee, Emily L.
ABSTRACT: Albright hereditary osteodystrophy (AHO) is caused by heterozygous inactivation of GNAS, a complex locus that encodes the alpha‐stimulatory subunit of heterotrimeric G proteins (Gsα) in addition to NESP55 and XL α s due to alternative first exons. AHO skeletal manifestations include brachydactyly, brachymetacarpia, compromised adult stature, and subcutaneous ossifications. AHO patients with maternally‐inherited GNAS mutations develop pseudohypoparathyroidism type 1A (PHP1A) with resistance to multiple hormones that mediate their actions through G protein‐coupled receptors (GPCRs) requiring Gsα (eg, parathyroid hormone [PTH], thyroid‐stimulating hormone [TSH], growth hormone–releasing hormone [GHRH], calcitonin) and severe obesity. Paternally‐inherited GNAS mutations cause pseudopseudohypoparathyroidism (PPHP), in which patients have AHO skeletal features but do not develop hormonal resistance or marked obesity. These differences between PHP1A and PPHP are caused by tissue‐specific reduction of paternal Gsα expression. Previous reports in mice have shown loss of Gsα causes osteopenia due to impaired osteoblast number and function and suggest that AHO patients could display evidence of reduced bone mineral density (BMD). However, we previously demonstrated PHP1A patients display normal‐increased BMD measurements without any correlation to body mass index or serum PTH. Due to these observed differences between PHP1A and PPHP, we utilized our laboratory's AHO mouse model to address whether Gsα heterozygous inactivation differentially affects bone remodeling based on the parental inheritance of the mutation. We identified fundamental distinctions in bone remodeling between mice with paternally‐inherited ( GnasE1+/−p ) versus maternally‐inherited ( GnasE1+/−m ) mutations, and these findings were observed predominantly in female mice. Specifically, GnasE1+/−p mice exhibited reduced bone parameters due to impaired bone formation and enhanced bone resorption. GnasE1+/−m mice, however, displayed enhanced bone parameters due to both increased osteoblast activity and normal bone resorption. These in vivo distinctions in bone remodeling between GnasE1+/−p and GnasE1+/−m mice could potentially be related to changes in the bone microenvironment driven by calcitonin‐resistance within GnasE1+/−m osteoclasts. Further studies are warranted to assess how Gsα influences osteoblast–osteoclast coupling. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.